Validação da versão adaptada transculturalmente da Family Impact of Assistive Technology Scale for Augmentative and Alternative Communication (FIATS-AAC-BR) - Lino, Carolina Cristina Alves (2023)
Considering the importance of searching for assertive methods and procedures in the implementation of Augmentative and Alternative Communication (AAC) systems with children and young people with complex communication needs, researchers and professionals have been dedicating themselves to exploring means and resources to enable a more effective evaluation regarding the intrinsic components to the impact of the quality of this process. This study is part of a bigger research that aims to translate and validate the Canadian scale Family Impact of Assistive Technology Scale for Augmentative and Alternative Communication (FIATS-ACC) for use in Brazil. This scale proposes to evaluate the impact in the daily family context of the use of AAC systems by children and adolescents with complex communication needs, based on the family‟s perception. A first study has already been carried out, which focused on the following theoretical procedures: initial translation, reconciled translation, content evaluation by specialists and back-translation. This research aims to carry out the face validation and preliminary validation of the psychometric properties as continuities of the cross-cultural validation process of the FIATS-AAC scale for the Brazilian Portuguese language. The methodological and cross-sectional research had as materials the scale, four instruments developed for the research, and an instrument used as a comparative measure to assess the convergent validity of the scale. Five parents/main caregivers of children/adolescents using the CAA participated in Face Validation. The data were descriptively tabulated and a comparative semantic analysis was performed, indicating that of the 89 items presented in the scale, five of them would have doubts for the respondents. From the adequacy of the items and with the agreement by the authors of the original scale, a reliability analysis was performed regarding the internal consistency and stability of the scale with 30 participants, who are characterized as the target audience of the FIATS-AAC-Br. These participants completed the Characterization Sheet and the FIATS-AAC-Br scale. After an interval of two weeks from the first application, the FIATS-AAC-Br scale was applied again, with the guarantee of verifying if there was agreement between the answers, thus attributing greater stability to the data, and in parallel, the PedsQl™ was administered together with to the first application, being used as a comparative measure to evaluate the convergent validity of the FIATS-AAC-Br. To check the instrument's internal consistency, Cronbach's alpha was calculated, indicating good internal consistency, since the result for the total FIATS-AAC-Br scale showed a level higher than the limit for internal consistency (α = 0.94 ) . As for stability, the Intraclass Correlation Coefficient (ICC) was calculated and the data indicated an excellent result for both the total FIATS-AAC-Br (ICC = 0.96; 95% CI = 0.92-0.98), as for its 13 dimensions. To assess the convergent validity, the Pearson Correlation Coefficient between the FIATS-AAC-Br and the PedsQl™ was calculated, and the data received a significant positive result (Pearson r= 0.719, p < 0.001). Thus, the results reach the objective proposed for the research and are expected to collaborate with the availability of a measurement tool to professionals and services that work with AAC in monitoring the proposed interventions.